CHARACTER VALUE EXPLORE IN LASKAR PELANGI AS A STRENGTHENING OF STUDENTS’ CHARACTER BUILDING - Resti Rumapea; Berlian Tambunan; Winda Yuliani Pardosi (English Language Teaching Prima Journal (ELT), 2021)
Abstract This study aims to determine the character values of students, examine whether the good characters in the Laskar Pelangi film can be applied in teaching and learning life, and apply moral values that can be used with qualitative descriptive methods. And reading which was used in collecting data, it was found that Laskar Pelangi is a film that teaches very good norms and moral values that can be expected for educational activities, especially teaching and learning. We hope that this research can make readers more motivated and make this research one of the teaching resources that can be applied in student character education. Keywords: Character building, Film, Character value